Ex vivo comparison of CBCT and digital periapical radiographs for the quantitative assessment of periodontal defects - Rütters, Maurice; Hagenfeld, Daniel; Sayed, Nihad el; Zimmermann, Nils; Gehrig, Holger; Kim, Ti-Sun (Clinical oral investigations, 2020)
Accurate imaging is essential for effective treatment planning in periodontology. The aim of this ex vivo study was to investigate the accuracy of cone beam computed tomography (CBCT) and digital periapical radiographs (PA) in imaging periodontal defects. Hypotheses are: 1. That CBCT is a more accurate method than PA concerning vertical measurements of periodontal bone defects2. That CBCT itself is an accurate method to describe vertical periodontal bone loss